2020
DOI: 10.1289/ehp6394
|View full text |Cite
|
Sign up to set email alerts
|

Flaring from Unconventional Oil and Gas Development and Birth Outcomes in the Eagle Ford Shale in South Texas

Abstract: BACKGROUND: Prior studies suggest exposure to oil and gas development (OGD) adversely affects birth outcomes, but no studies have examined flaring-the open combustion of natural gas-from OGD. OBJECTIVES: We investigated whether residential proximity to flaring from OGD was associated with shorter gestation and reduced fetal growth in the Eagle Ford Shale of south Texas. METHODS: We conducted a retrospective cohort study using administrative birth records from 2012 to 2015 (N = 23,487) and satellite observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 59 publications
(121 reference statements)
2
40
0
Order By: Relevance
“…In Texas, Whitworth et al used Dallas-Fort Worth area birth records, where they observed no clear associations between drilling activity and odds of an SGA infant and inverse but not significant associations for drilling activity and decreased term birth weight (Whitworth et al 2017). Cushing et al also used Texas birth records and demonstrated that some of the association between residential proximity to drilling and reduced term birth weight is attributed to natural gas flaring (Cushing et al 2020), the process by which economically nonviable natural gas is extracted and combusted (Elvidge et al 2009;Franklin et al 2019). In Colorado, McKenzie et al used birth records and observed small protective associations with preterm birth and term low birth weight for infants whose mothers resided near natural gas drilling during pregnancy (McKenzie et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In Texas, Whitworth et al used Dallas-Fort Worth area birth records, where they observed no clear associations between drilling activity and odds of an SGA infant and inverse but not significant associations for drilling activity and decreased term birth weight (Whitworth et al 2017). Cushing et al also used Texas birth records and demonstrated that some of the association between residential proximity to drilling and reduced term birth weight is attributed to natural gas flaring (Cushing et al 2020), the process by which economically nonviable natural gas is extracted and combusted (Elvidge et al 2009;Franklin et al 2019). In Colorado, McKenzie et al used birth records and observed small protective associations with preterm birth and term low birth weight for infants whose mothers resided near natural gas drilling during pregnancy (McKenzie et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Third, research on the overall toxicology and health effects of hydrocarbon production could aid in identifying both the broad effects of hydrocarbon production on humans and the effects of specific activities and contaminants. Recently, Cushing et al (2020) examined the impact of natural gas flaring on birth outcomes; results suggested that exposure to flare events was associated with 50% higher odds of preterm birth. In a review of the potential health effects of UOG development, the Health Effects Institute (HEI, 2020) emphasized that more studies are needed with the objective of quantifying potential human exposure to water contamination from UOG processes.…”
Section: Conclusion and Opportunities For Future Researchmentioning
confidence: 99%
“…Additionally, we need more studies of the potential disproportionate environmental health impacts on different populations with regard to race, ethnicity, socioeconomic vulnerability, and urbanity/rurality, because certain subgroups may experience more pronounced responses due to greater cumulative burdens of multiple socioenvironmental stressors (Kroepsch et al 2019;Payne-Sturges et al 2021). The need for additional environmental justice-focused analyses is supported by findings from Willis et al and by a study of birth outcomes and flaring from oil and gas wells in the Eagle Ford Shale of Texas that reported that adverse effects appeared to be disproportionately borne by Hispanic women (Cushing et al 2020).…”
mentioning
confidence: 99%